Jenis Kupu-kupu di Cagar Alam Imogiri Kabupaten Bantul Daerah Istimewa Yogyakarta - Nur Surantiwi; Raditia Nugraha; Dyahning Retno Wati; Icha Arzika (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2025)
Imogiri Nature Reserve established as conservation area that protected by act and state, which has ecosystem to maintain its biodivesity. The study of butterfly diversity was conducted in January – Desember 2024, to determine the existence of butterflies in Imogiri Natural Reserve. Observation was conducted with Visual Encounter Survey in the morning and late afternoon while doing patrol in 4 area. Species identification were compared with ilustration and description using Kupunesia application and field guide. Therefore, 51 species Butterflies in 5 Family were identified exist in Imogiri Natural Reserve. There was 7 species of Papilionidae,9 species Pieridae, 6 species Lycaenidae, 27 species Nymphalidae and 2 species Hesperiidae. The most encountered Butterfly was Family Nymphalidae. Many species of Nymphalidae mimic other species to protect themselves from predators. Members of this family are easily found in the Imogiri Nature Reserve with many host plants such as types of Ficus sp. and Memecylon sp. The most abundant species Family Nymphalidae is Euploea sylvester, which in terms of color is very suitable for environmental conditions so that it can mimic. The poisonous Euploea sylvester comes from the caterpillar's food, namely the Apocynacea plant.Butterfly encounters are most often found in the Protection Block as its function is to protect flora and fauna and is limited only to research activities.